Reduced-Threshold Emission of Capillary Filled by Doped-Dye Cholesteric Liquid Crystals With Photo-Alignment Polyimide Films - Yue-Lan Lu; Xiang-Bao Yin; Zuo-Ren Xiong; Yue Yang; Wei-Min Sun; Yong-Jun Liu (IEEE Photonics Journal, 2018)
A microcavity laser is reported using dye-doped cholesteric liquid crystals (CLCs) filled in a glass capillary with photo-alignment polyimide films. This laser runs based on the properties that a CLC has a refractive index much higher than that of glass, so whispering-gallery-mode (WGM) laser and distributed-feedback-mode lasers are included in the emission spectrum. We obtain a low threshold energy of $4.5\;μ {\rm{J}} · {\rm{puls}}{{\rm{e}}^{ - 1}} · {\rm{m}}{{\rm{m}}^{ - 2}}$ , establish the shift of 3.04 nm of the WGMs in the temperature range 43–48 °C, and investigate electric field tunability.